Prognostic Value of Ki-67 Index in Patients With Endometrial Stromal Sarcoma - Meng, Yu; Quan, Quan; Zhang, Fenfen; Liu, Yao; Ren, Siling; Mu, Xiaoling (Frontiers in Medicine, 2022)
Objective The Ki-67 index is used to evaluate cell proliferation activity, which is related to tumor progression, metastasis, and prognosis. We aimed to explore the prognostic value of Ki-67 index in endometrial stromal sarcoma and to explore the optimal cut-off value of Ki-67 index for predicting recurrent endometrial stromal sarcoma. Methods A total of 82 patients with endometrial stromal sarcoma who were treated in our hospital were collected. Clinicopathological data of these patients were retrospectively analyzed. Ki-67 index was detected by the immunohistochemical method. Receiver operating characteristic curve and the Youden index were performed to determine the optimal cut-off value of Ki-67 index for predicting recurrent endometrial stromal sarcoma. The Cox regression was performed to analyze risk factors affecting prognosis of endometrial stromal sarcoma. The Kaplan–Meier method and Log-rank test were performed to analyze the survival of patients. Results The optimal cut-off value of Ki-67 index for predicting recurrent endometrial stromal sarcoma was 35%. The results of univariate analysis showed that high Ki-67 index (≥35%) was statistically significantly bound up with shorter progress free survival and overall survival. The results of multivariate analysis showed that Ki-67 index (P = 0.001) and ovarian preservation (P = 0.040) were independent prognostic factors of progress free survival. Conclusions A Ki-67 index cut-off of 35% was optimal for predicting recurrent endometrial stromal sarcoma. Ki-67 index may be a useful prognostic marker in endometrial stromal sarcoma.